A THEORETICAL CONTRIBUTION OF SME MANAGER’S OVERCONFIDENCE BIAS IN WORKING CAPITAL MANAGEMENT AND PERFORMANCE - Jeff, Lamptey; Asri, Bin Marsidi; Lonas, Ladime (Allied Business Academies, 2021)
We argue that managerial overconfidence bias affects working capital management. Overconfident SME managers overestimate their sales growth and underestimate the volatility of cash flow of their firms and thus overinvest in inventory for higher returns if they have enough personal capital or cheaper sources of external capital. An overconfident SME manager will overinvest because of the transactional motive, market signaling effect and market leadership motive. We describe SME managers as overconfident if the person claims to have superior financial ability, perfect industry knowledge and is optimistic in business and thus systematically fail to reduce their personal exposures (maximization wealth) to their firms’ specific risks. Thus, overconfidence can serve as useful framework for most SME managers who make working capital decisions, particularly inventory based on their personal characteristics.